Pharmacoeconomic considerations in the treatment of breast cancer - Athanasios Pallis; Vasiliki Tsiantou; Efi Simou; et al (Dove Medical Press, 2010)
Athanasios Pallis1, Vasiliki Tsiantou2, Efi Simou3, Nikos Maniadakis41Department of Medical Oncology, University General Hospital of Heraklion, Crete; 2Department of Health Economics, 3Department of Epidemiology and Biostatistics; 4Department of Health Services Organization and Management, National School of Public Health, Athens, GreeceAbstract: Breast cancer is the most common malignancy in women worldwide and causes great economic burden. The aim of this paper is to present the available clinical and pharmacoeconomic evidence associated with different therapies for breast cancer. As significant progress was made in recent years and there are many alternative treatments, which are indicated according to the stage and the type of the disease, the age and health status of patient, and vary from surgery to hormonal treatment and chemotherapy. A broad literature review was undertaken and the paper presents the evidence available regarding the effectiveness and cost-effectiveness of the alternative options. Despite the high cost of most therapies and perceptions that treatments in this area may not be cost-effective, due to a combination of high costs and short survival, based on the literature review treatment options for breast cancer are in general deemed to be cost-effective. Time horizon, stage of the disease, patient age, therapy onset, benefit duration and time to recurrence may influence the results. Pharmacoeconomic analyses of alternative therapy options will improve decision-making and will help to optimize the use of scarce health care resources allocated to the care of breast cancer patients.Keywords: breast cancer, cost, pharmacoeconomics